Respuesta :

5ever
To solve for d, you need to get d by itself on one side of the equals sign!

Since d + c/b is currently on one side of the equals sign, all you have to do is move the c/b to the other side of the equation (to the other side of the equals sign with the a).

To do this, you should subtract c/b from both sides of the equation.

You then get:

a - c/b = d

D is now by itself - you solved for d and your work is done.

Answer:

d=ab-c

Step-by-step explanation:

First, multiply each side of the equation by  b  to eliminate the fraction and keep the equation balanced:

b x a = b x d+c/b

ab= b x d+c/b

ab= d+c

Now, subtract  c  from each side of the equation to solve for  d  while keeping the equation balanced:

ab - c = d + c - c

ab - c = d + 0

ab - c = d

d = ab - c